CURRENT POSSIBILITIES OF USE OF INDIRECT CALORIMETRY IN PERIOPERATIVE ENERGY MONITORING - V.I. Cherniy; A.I. Denysenko (Клінічна та профілактична медицина, 2020)
The purpose of the study is to develop a method of perioperative energy monitoring and to implement it in clinical practice.